A potentially contentious case of correction under Article 32.5.1.1 of the International Code of Zoological Nomenclature - Dickinson, Edward C.; David, Normand; Gregory, Steven M. S. (Zootaxa, 2009)
On page 188 of the same number[1] of the journal volume in which the above pair of names appeared a corrigendum specifies: ‘P. 163. Line 7, erase the words “brachypterus or”’. This action by Gould’s publisher introduced a correction that leaves macrorhynchus as the correct original spelling, and this was also used in the index of the volume. It should be observed that the correction is also consistent with Gould’s description ("rostro praegrandi", "bill ... also projects much farther…than in any other species inhabiting Australia"), and with the lack of a comment therein on wing length. Gould (1865: 89) used "brachypterus" (which could be viewed as a First Reviser act under Art. 24.2.4), and Mathews (1912: 282) selected "brachypterus" (which could be viewed as a First Reviser act under Art. 24.2.3), but these later acts are unnecessary and nullified as the precedence of the spelling macrorhynchus is objectively determined under Arts. 24.2.5 and 32.5.1.1 combined with Art. 86.3. [1] Duncan (1937) dated pages 119–188 ‘July 1841’.